Estado Novo em cena: a atuação do interventor João Punaro Bley e a articulação das elites políticas no Espírito Santo (1937-1945) - Barcelos, Gabriela Loureiro (2019)
This research aims to investigate the performance of João Punaro Bley during the Estado Novo, emphasizing the relationship between interventoria and political elites. Initially, we sought to contextualize Era Vargas at the national and regional levels, we identified the intellectual field in support of the Estonian reforms, in order to understand the intellectual apparatus used in political praxis. In addition, we investigated the reception of the Vargas project in Espírito Santo from studies already done, in addition to the dialogue with the sources. The entire investigative proposal of this work was possible from the identification of the members of this elite and the mechanisms of action within state power. Thus, we seek to recreate the networks of contact and action between elites and interventoria, understanding the public offices as the field in which these forces established themselves. As a source we used documentation still unexplored in the studies about the Era Vargas in Espírito Santo - Espírito Santo Governance Fund - radiograms, telegrams and trades, besides the manuscript and interviews of the intervener, as well as some periodicals of the time: magazine Vida Capichaba and the newspaper Diário da Manhã. Faced with this abundant documentation, we established content analysis as the main methodological resource, as well as the theory of sociability networks to recognize the articulations necessary for the readaptation of the elites in the spaces of power and the intervention of the interventoria. Our hypothesis guided the construction of this work, it consists of realizing that part of the political elite, including that of forces opposed to Vargas, were relocated in the power spaces, going against the discourse of rupture to regionalisms, characteristic of the Estado Novo. As for the theoretical aspects, we rely mainly on the concepts of symbolic power to understand the action between interventor and elites; field in order to perceive the strategies and resources used to occupy the spaces of power; and elites, fundamental concept to identify the origin and the strength of the groups before a new moment in the Brazilian political history, that was the Estado Novo.